A case report of an elderly with herpes zoster and atrial fibrillation taking warfarin - Putra, Gilang; Devina, Wilona; Priyadarshini, Ida Ayu Uttari (Explorer Front, 2024)
Background: Herpes zoster (HZ) presents with unilateral dermatomal pain and rash resulting from the reactivation and proliferation of latent varicella zoster virus (VZV) that dwells in neurons following varicella. It mostly occurs in the elderly and in immunocompromised . Warfarin consumption can lead to dysregulation of cytokines that cause immune dysregulation, which can be a factor in the reactivation of herpes zoster. There is limited research or study exploring the correlation between herpes zoster reactivation and the use of warfarin in patients with atrial fibrillation This case report aim to investigate potential role of anticoagulant therapy, specifically warfarin, in the reactivation of HZ in elderly patients, and to explore the implications of polypharmacy and immune dysregulation in the management and prevention of HZ. Case Description: A 55-year-old male with a history of atrial fibrillation, currently on warfarin, was admitted with complaints of pain blister lession that developed 7 days post-discharge from the Cardiology department. His initial symptoms included pruritus and pain localized to the chest and right thoracic area. Dermatological examination revealed herpetiform vesicles on an erythematous base, accompanied by crusts and scabs, distributed along thoracic dermatomes T6-T8. Conclusion: Elderly patients often experience polypharmacy due to degenerative diseases. Cardiovascular treatment often includes anticoagulants such as warfarin. Following 1 week after the administration of topical antibiotic and steroid ointments, the patient demonstrated a positive clinical outcome with a few complications after HZ infection.